Leaf Surface Micromorphology in Hybrids of Wheat and ×Trititrigia × Elymus farctus - Alexander V. Babosha; Pavla O. Loshakova; Alina A. Pogost; Margarita M. Gevorkyan; Anastasia D. Alenicheva; Galina I. Komarova; Tatyana S. Wineshenker; Irina N. Klimenkova; Vladimir P. Upelniek (Agronomy)
The leaf surface micromorphology and the size of the stomatal complex of hybrids in the eighth seed generation from the crossing of ×Trititrigia cziczinii × Elymus farctus (f11814) on the wheat-like wheat-wheatgrass hybrid w107 were investigated by performing scanning electron microscopy of frozen samples (cryoSEM). The micromorphological characteristics of the paternal plants (w107) were dominant in the hybrid leaves. Costal long cells with silicified wavy walls, characteristic of w107 but absent in the mother plants f11814 and E. farctus, were observed in all hybrid samples examined. Conversely, shield-shaped prickles, a characteristic feature of E. farctus, were retained only in some hybrids. In addition, the maternal feature of Ω-shaped junctions of long epidermal cells in the intercostal zone was completely absent in hybrids. Quantitative parameters of the stomatal apparatus showed a weak correlation with micromorphological markers. Stomatal density on the adaxial side was inversely correlated with stomatal size, while variation in these parameters on the abaxial side occurred independently. The prevalence of paternal micromorphological traits in the hybrids seems to be a consequence of the elimination of genetic material from E. farctus, analogous to the loss of chromosomes from wild species observed in other distant crosses.